The Cumulative Impact of International Motor Racing Running on the Regional Entrepreneurial Development in the Case of Krasnodar Region - Andrey B. Ilin (Модернизация, инновация, развитие, 2017)
Purpose: the purpose of this paper is to identify the effects from holding the world championship "Formula One" on the territory of Krasnodar Krai on regional nationwide scales. Methods: the methodological framework of this paper comprises: content analysis, public analysis findings in the sphere of sports business organizations development, empirical and sociological (enumeration) methods. Results: in this regard, the author of this paper identifies a multiplicative effect from the operation of a global company "Formula One" in Russia through the prism of fashion, social, economic, industrial, infrastructure, investment and integration effects. This allows to draw a conclusion that "Formula One" in Russia as a sports and entertainment mega-event leads to the development of the national economy through small and medium business over race service and arrangement (recreation, hotel complex, restaurants, cafes, entertainment complexes, shopping malls, transportation terminals, railway interchange, additional points in the airport and etc.). It is proved that Sochi profile as a world-famous resort encourages the emerging of additional businesses. These and other factors allow Sochi to solve the economic problem of the post-Olympic heritage. The effects of “Formula One” on nationwide and regional scales are represented by a diagrams. Conclusions and Relevance: practical implications of current paper lies in the justification of provisions and conclusions in order to understand the importance of "Formula One" stage in Russia, the need for its promotion and revitalization of economic entities interest to the territories development.